Optimaliasasi Keuntungan Pada Penjualan Cireng Isi Menggunakan Pemprograman Linear Metode Simpleks - Eva Julia Santika; Muhammad Fikri Ramadhan; Padli Saputra Pratama; Risma Apriliyanti (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
Cireng comes from the Sundanese region with the acronym of aci digoreng "fried tapioca" which is made by frying a mixture of dough made from tapioca flour. Currently, cireng is sold in various flavors and forms, such as chicken, beef, sausage, meatballs, to cheese and teriyaki chicken. Even innovation is not only in taste but also in form, for example cimol, cilung, and others. In this case, the author conducted a study on an UMKM called Cireng Isi Seblak Brother which has more than 30 variants. With the best-selling variants being shredded chicken and tetelan. The purpose of this case study is to maximize the calculation of the maximum profit that should be and that occurs in the field.